Enhanced efficacy of immune checkpoint inhibitors combined locoregional therapy and tyrosine kinase inhibitors in the treatment of unresectable hepatocellular carcinoma: A single - center retrospective study - Bu, Junfeng; Li, Zihan; Hu, Die; Lan, Ling; Huang, Jiwei; Wang, Xin; Li, Qiu; Zhou, Jin; Zeng, Yong (Frontiers in Oncology, 2025)
BackgroundUnresectable hepatocellular carcinoma (HCC) presents significant treatment challenges. While locoregional therapies (LT) and tyrosine kinase inhibitors (TKI) offer some benefits, prognosis remains poor. Immune checkpoint inhibitors (ICI) have shown promise in other oncological settings, suggesting potential benefits in HCC treatment regimens.MethodsThis retrospective study analyzed 232 patients diagnosed with unresectable HCC at West China Hospital from January 2019 to December 2023. Patients were categorized into two treatment groups: LT+TKI and LT+TKI+ICI. All patients underwent standardized locoregional treatments and first-line TKIs, with the latter group also receiving ICIs. The primary endpoints measured were overall survival (OS) and progression-free survival (PFS). Survival analysis utilized Kaplan-Meier estimates and Cox regression models.ResultsThe LT+TKI+ICI group demonstrated significantly improved survival outcomes compared to the LT+TKI group. Median OS was 28 ± 3.9 months in the LT+TKI+ICI group versus 21 ± 3.0 months in the LT+TKI group, with corresponding 6-, 12-, and 24-month OS rates of 96.8%, 79.3%, and 59.4% versus 85.8%, 71.5%, and 44.1%, respectively (HR, 0.64; 95% CI, 0.449-0.913; P = 0.014). Median PFS also favored the LT+TKI+ICI group (11 ± 1.1 months vs. 7 ± 0.76 months; HR, 0.60; 95% CI, 0.452-0.805; P<0.001). Multivariable analysis identified LT+TKI, vascular invasion, and metastasis as independent risk factors for poorer survival outcomes.ConclusionsAdding ICI to LT and TKI significantly extends both OS and PFS in patients with unresectable HCC. These findings suggest that integrating ICI into treatment protocols could be beneficial in managing unresectable HCC, particularly for patients with vascular invasion.